2003
DOI: 10.1080/1462220031000118568
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of susceptibility to smoking and ever smoking: A longitudinal study in a triethnic sample of adolescents

Abstract: This report describes a longitudinal study of the natural course of smoking initiation in a school-based, ethnically diverse (42% White, 37% African American, 20% Hispanic) sample of adolescents in grades 5, 8, and 12 who were followed prospectively for 1 year. A cohort of 659 students was identified who were never smokers at baseline and who completed questionnaires both at baseline and at 1-year follow-up. From this cohort, predictor variables were used to identify ethnic-specific risk factors for (a) "susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
77
2
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(92 citation statements)
references
References 0 publications
9
77
2
4
Order By: Relevance
“…Consistent with our findings, results from Memetovic et al (2016) indicated that higher sensation seeking scores were associated with significantly higher odds of intention to use cigarettes after for covariates in a sample of eighth and ninth grade Canadian adolescents. To date, no study has examined factors associated with change in susceptibility to e-cigarette use, and research with respect to change in susceptibility to conventional cigarette use among adolescents has not examined sensation seeking as a predictor (Forrester, Biglan, Severson, & Smolkowski, 2007; Gritz et al, 2003; Weiss et al, 2006). Notably, both Forrester et al (2007) and Gritz et al (2003) found that different factors predicted change in susceptibility to smoking versus change in smoking behaviors (initiation of smoking, transition to regular smoking), thus suggesting that different mechanisms may influence change from one stage to another along the tobacco use continuum.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, results from Memetovic et al (2016) indicated that higher sensation seeking scores were associated with significantly higher odds of intention to use cigarettes after for covariates in a sample of eighth and ninth grade Canadian adolescents. To date, no study has examined factors associated with change in susceptibility to e-cigarette use, and research with respect to change in susceptibility to conventional cigarette use among adolescents has not examined sensation seeking as a predictor (Forrester, Biglan, Severson, & Smolkowski, 2007; Gritz et al, 2003; Weiss et al, 2006). Notably, both Forrester et al (2007) and Gritz et al (2003) found that different factors predicted change in susceptibility to smoking versus change in smoking behaviors (initiation of smoking, transition to regular smoking), thus suggesting that different mechanisms may influence change from one stage to another along the tobacco use continuum.…”
Section: Discussionmentioning
confidence: 99%
“…Smoke-free legislation may alter social norms by decreasing visibility and perceived acceptability of smoking in public venues and lead people to change their beliefs, awareness, attitudes, and practices concerning smoking. 26,27 Behavioral susceptibility theory argues that if a given behavior becomes inconvenient or difficult, this behavior will gradually decline. 27,28 Indeed, research demonstrates that smoking restrictions in public places inform people about current social norms toward smoking, and that greater perceived social unacceptability is associated with reduced cigarette consumption.…”
Section: Effects Of Enactment Of Legislative (Public)mentioning
confidence: 99%
“…26,27 Behavioral susceptibility theory argues that if a given behavior becomes inconvenient or difficult, this behavior will gradually decline. 27,28 Indeed, research demonstrates that smoking restrictions in public places inform people about current social norms toward smoking, and that greater perceived social unacceptability is associated with reduced cigarette consumption. 26 A second, somewhat more pessimistic, theoretical model is that of displacement or last refuge which posits that smoking bans in public places will displace smoking behaviors to private places, like homes, and will produce undesired effects such as increased SHS exposure for nonsmoking family members.…”
Section: Effects Of Enactment Of Legislative (Public)mentioning
confidence: 99%
“…While this index consistently identifies teens with double the risk of starting to smoke (U.S. Department of Health and Human Services, 2012), the proportion of true positives (sensitivity) over the subsequent four years is a low one third of future smokers (Choi, Gilpin, Farkas, & Pierce, 2001; Gritz et al, 2003). This at-risk measure index would be more useful for the development of effective population interventions if it identified more than half of future smokers.…”
Section: Introductionmentioning
confidence: 99%